Digitalisasi Akuntansi dan Transformasi Nilai Budaya: Adaptasi Sosial UMKM di Kota Tangerang - Florencia Irena Lawita; Dading Damas Ario Wicaksono; Teguh Yanto; Irvan Bayu Pratama; Eveline Mischeilla Yolanda (Politeknik Ganesha Medan, 2026)
This study aims to examine how accounting digitization contributes to cultural value transformation and social adaptation among Micro, Small, and Medium Enterprises (MSMEs) in Tangerang City. The focus of the study lies on the determining factors of adoption, such as financial and digital literacy, perceived benefits, infrastructure availability, and implementation costs. The research method used is a qualitative approach through in-depth interviews with a number of MSME actors from various business sectors. The results show that digital literacy is a key factor in increasing MSME actors' understanding of the use of accounting applications. Overall, this study confirms that the success of accounting digitization in MSMEs does not only depend on technological aspects, but also on social support, cultural adaptability, and policies that support digital inclusiveness. These findings are expected to provide practical contributions to the development of MSME empowerment strategies and enrich the literature on the integration of technology and culture in accounting practices.